Ta’zie (Religious Theatre) vs. Noruz (the New Year and its Rituals): The Politics of the Intangible Cultural Heritage of Humanity in Iran - Bromberger, Christian (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
Above and beyond a legitimate concern with preserving intangible cultural “treasures” and “masterpieces,” what are the extra-heritage issues that tend to slip beneath UNESCO’S applications for recognition and listing? Through an examination of recent projects presented by Iran, the author proposes to carry out a modest ethnography that addresses the meaning of these applications, ethnography being in the words of Clifford Geertz (Geertz 1983: 152), “an enterprise […] whose aim is to render obscure matters intelligible by providing them with an informing context.”